True blood : The complete 4th season, disc 1 - Paquin, Anna.; Moyer, Stephen; Wesley, Rutina; Kwanten, Ryan, 1976-; Trammell, Sam, 1971-; Skarsgard, Alexander; Ellis, Nelsan; Ball, Alan, 1957-; Harris, Charlaine; Home Box Office (Firm); HBO Entertainment (Firm); Warner Home Video (Firm) ([New York] : Home Box Office ; Burbank, CA : Distributed by Warner Home Video, 2012)
Another supernatural force has come to light in Bon Temps - witchcraft - and life for its residents will never be the same. Sookie finds herself entangled in a love triangle - torn between a vengeful Bill, the new Vampire King of Mississippi, and Eric, who's not the former Viking he once was. Led by a charismatic witch named Marnie, who threatens to let no one living or dead stand in her way, a powerful coven tempts Lafayette, Tara, and Jesus with otherworldly powers. Jessica tries to adjust to a domestic life, while Jason finds himself alone in werepanther territory. Arlene and Terry come to terms with their highly unusual baby, and Alcide finds himself caught in the clutches of an old flame.
Originally broadcast as single episodes of a television series in 2011.
Special features: Inside the episodes; "True Blood : the final touches"; audio commentaries.
Based on the Sookie Stackhouse novels by Charlaine Harris.
Anna Paquin, Stephen Moyer, Sam Trammell, Ryan Kwanten, Rutina Wesley, Alexander Skarsgard, Nelsan Ellis.
CHVR: 18A.
DVD, widescreen; Dolby Digital 5.1.
Keywords: Stackhouse, Sookie (Fictitious character) -- Drama; Vampires -- Drama; Werewolves -- Drama; Supernatural -- Drama; Man-woman relationships -- Drama; Drama; Fantasy television programs; Horror television programs; Video recordings for the hearing impaired